Remote control laboratory for DSP-controlled induction motor drives - Tekin, Ahmet; Ata, Fikret; Gokbulut, Muammer (Wiley, 2012)
This article presents an Internet-based remote laboratory for digital signal processor (DSP)-controlled induction motor (IM) drive. The remote experimental rig uses MATLAB/Simulink compatible dSPACE DS1104 signal processor to realize the control algorithm, current control, and PWM modulation. MATLAB Real-Time Workshop (RTW) environment provides the real-time operation using a PC and I/O boards and, therefore, application files required for conducting the experiment in laboratory environment can be prepared with the RTW and dSPACE real-time interface (RTI). Also a graphical-user interface can be designed using the dSPACE ControlDesk Developer (CDD). However, for implementation of remote laboratory, interface software between local application and remote users should be developed, since the MATLAB Web Server (MWS) does not allow online access to some hardware such as DS1104 used in this study. For this purpose, an interface using the Python code is developed for remote automation of the ControlDesk. Furthermore, serverclient communication software with Delphi programming language is developed for remote implementation of the experiment. Using the user-friendly interface, the Internet-based remote laboratory allows the students to conduct the experiment by changing the predefined control parameters online or uploading the controller designed by the user and then to observe system responses in numerical, graphical, or video format on the remote computer. (C) 2010 Wiley Periodicals, Inc. Comput Appl Eng Educ 20: 702712, 2012
Keywords: remote laboratory; Internet-based laboratory; digital signal processor; induction motor